Construction Process of the Original Road on Jl. Raya Waled Desa – Jl. Raya Jatimulya, Mekarjaya, Waled Subdistrict, Cirebon Regency - Isradi, Muhammad; Ruhiat, Nur Aini; Pagit, Salsa Baidillah; Prasetio, Muhammad Fahrul; Sudrajat, Kukuh Mahi (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Road infrastructure design is an important aspect of regional development, especially in areas with high mobility such as Waled District, Cirebon Regency. This study aims to redesign the ±2.8 km section of Jl. Raya Waled Desa – Jl. Raya Jatimulya, Mekarjaya to meet the geometric standards for secondary collector roads as stipulated by the Directorate General of Highways. The research method was conducted through field surveys to obtain primary data on existing road conditions, topography, drainage, and traffic flow, which were then analyzed using civil engineering software such as Autodesk Civil 3D. The analysis results showed that the average width of the existing pavement was 5.5 meters with moderate to severe damage, so it needed to be widened to 6 meters to meet the standards. The maximum slope value of 3.2% is still within tolerance limits, but several points require elevation improvements to overcome flooding. Curve analysis shows that several segments have a radius of less than 90 meters, so superelevation improvements and curve widening are needed to ensure vehicle safety. Traffic load calculations (ESA5) show a total design load of 6,491,947 ESA (left direction) and 8,712,590 ESA (right direction), which are used as the basis for pavement thickness planning. In addition, a hydrological analysis using the Manning method resulted in a channel capacity of 1,643 m³/second with a flow velocity of 0.6 m/second, indicating that the drainage system needs improvement to accommodate rainwater runoff.